2006
DOI: 10.1063/1.2163627
|View full text |Cite
|
Sign up to set email alerts
|

Terrace width dependence of cobalt silicide nucleation on Si(111)-(7×7)

Abstract: Articles you may be interested inMetal-cluster growth with asymmetric diffusion and reversible aggregation on Si ( 111 ) 7 × 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Characteristic properties of vicinal surfaces, such as the highly anisotropic diffusion ͑4-5 times higher diffusion barriers at steps 14 ͒ or the discontinuity of the stress field at steps, generally force a high aspect ratio, and hence limit the generation of homogeneous and symmetric islands. 15 These could be limiting factors in the growth of CoSi 2 quantum dots on vicinal surfaces with terraces beyond 250 Å, 8 but not in terraces below 100 Å. In the latter, faster kinetics due to the presence of abundant reactives could lead to a more efficient CoSi 2 epitaxy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic properties of vicinal surfaces, such as the highly anisotropic diffusion ͑4-5 times higher diffusion barriers at steps 14 ͒ or the discontinuity of the stress field at steps, generally force a high aspect ratio, and hence limit the generation of homogeneous and symmetric islands. 15 These could be limiting factors in the growth of CoSi 2 quantum dots on vicinal surfaces with terraces beyond 250 Å, 8 but not in terraces below 100 Å. In the latter, faster kinetics due to the presence of abundant reactives could lead to a more efficient CoSi 2 epitaxy.…”
mentioning
confidence: 99%
“…The use of stepped Si͑111͒ as a template to nucleate disilicide nanoislands was already tested using surfaces with terrace sizes varying from 250 to 700 Å and solid phase epitaxy. 8 It has been claimed that terraces in the 250-400 Å range have an adverse effect on the adatom diffusion, acting against shape transition and formation of flattop silicide islands. In contrast to this conclusion, here we demonstrate that the stabilization of flattop CoSi 2 nanoislands with controllable size and density can be actually achieved during RE of Co and using vicinal Si͑111͒ surfaces with relatively narrow ͑ϳ40-100 Å͒ terraces.…”
mentioning
confidence: 99%
“…For example, the chemical synthetic works of semiconductor nanocrystals and silver nanowire 1-3 and ordered array of nanostructures were fabricated by using the technique of electron beam lithography. [4][5][6] Recently, deposition of metals on semiconductor [7][8][9][10][11][12] or insulating oxide surface [13][14][15][16][17][18][19][20] was also used to grow nanoparticles or nanodots with great size uniformity.…”
mentioning
confidence: 99%
“…Zilani et al have reported that in their experiment the CoSi 2 nanocrystal islands were located along the upper step-edges, prevented from crossing into the bunch by the Ehrlich-Schwoebel barrier. 22 However, Figure 1(c) clearly shows that the nanocrystals reside at the step-bunches themselves, rather than at the upper terraces. Even those, whose upper side begins at a terrace, continue downwards, with their lower part residing at the step-bunch.…”
Section: Solid-phase Epitaxymentioning
confidence: 94%